A HISTORICAL OUTLINE OF RADIONUCLIDE CONTAMINATION OF THE YENISEY FLOODPLAIN BASED ON LANDSCAPE AND RADIOMETRIC SURVEY - Vitaly Linnik; Elena Korobova; Justin Brown (Geography, Environment, Sustainability)
Distribution of technogenic radionuclides discharged by the Krasnoyarsk Mining and Chemical Combine (KMCC, Zheleznogorsk) in the period from 1958 to 1992 has been studied in floodplain landscapes of the Yenisey river. After shutting down the direct-flow reactors the radioactive contamination of the Yenisey river became dozen times lower. Performed landscape and radiometric studies revealed factors responsible for radionuclide differentiation and the character of radionuclide distribution within two landscape segments of the Yenisey river floodplain. The first segment characterized the impact zone from 16 km to 20 downstream the discharge, the second one was studied in the remote zone as far as 2000 km down the river. Artificial radionuclide contamination was most intensive in the 60-ies of the past century when it reached the Kara Sea. Traces of that contamination were registered in soils of both sites at the depth of 20–50 cm.